Harmonisasi dan Disparitas: Pembagian Warisan bagi anak Angkat dalam Hukum Islam dan Hukum Perdata - M. Iqbal; Andina Larasati; Anisa Putri; Dewi Wulandari; Enjelita Dwi Maharani; Fahira Silva Dilla Nst; Lisa Alfira Andini; Nia Anjunita Sari Purba; Sri Muallimah; Theresia Mardiyana Tamba (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
Inheritance involving adopted children often becomes a complex and controversial issue in Indonesia’s dual legal system. In Islamic law, inheritance is strictly based on blood and marital relationships; therefore, adopted children are not considered legal heirs. To address this limitation, Article 209 of the Compilation of Islamic Law (KHI) introduces the concept of a wasiat wajibah or mandatory will, allowing adopted children to receive up to one-third of the adoptive parents’ estate. In contrast, civil law treats adopted children as equivalent to biological children if the adoption is legally recognized, granting them full inheritance rights. These contrasting provisions create legal disparities and confusion within society. This study aims to explore the different legal treatments of adopted children under both systems, identify the challenges they face, and analyze efforts toward harmonization. Using a qualitative, normative-juridical approach through literature and regulatory analysis, the study finds that Islamic law restricts inheritance through gifts and wills, while civil law ensures equal rights. Challenges include legal uncertainty, inconsistent judicial interpretations, and potential conflicts between adopted and biological heirs. Harmonization efforts are reflected in KHI provisions, legal reforms on adoption, and judicial practices seeking to balance sharia principles, social justice, and legal certainty.